Transforming Arab Economies : The Knowledge and Innovation Road - Utz, Anuja; Aubert, Jean-Eric (World Bank, Washington, DC, 2013)
Knowledge has always been central to development. A thousand years ago the Arab civilization led the world in knowledge, prosperity, and development. More generally, the Arab world is currently undergoing a transition on three fronts: 1) a political transition, which seeks to replace authoritarian powers with more democratic ones; 2) a social transition in which equitable programs to protect the poor will substitute for inefficient policies promoting public sector-based employment and the subsidization of basic goods; and 3) an economic transition in favor of more competitive and productive economic regimes. The report focuses on the economic side of this transition. On which areas must leaders of the Arab countries concentrate in order to stimulate growth, create jobs, restore trust, and provide a measure of hope and prosperity for their people? This is a humble effort to try and answer some of these questions in an integrative framework that puts knowledge and innovation-related policies at center stage.